EDUCAÇÃO E PROMOÇÃO DA SAÚDE: Avaliação da Saúde Bucal em Escolares de uma Comunidade do Município de São Luís – MA - VIANA, Maria Wilma Lacerda (2024)
Introduction: Despite the principle of integrality of the Unified Health System of Brazil, Primary Care still lacks financial investment, especially in relation to the oral health of the vulnerable population. Caries, one of the most prevalent chronic diseases in the world, affects individuals of all ages and is responsible for the early loss of teeth, which leads to physical and mental damage as it affects nutritional status, raises low self-esteem and predisposes the individual to systemic infections. Objectives: To evaluate the oral health conditions of schoolchildren of one institution in the city of São Luís - Maranhão, Brazil and to promote educational actions. Methodology: The study was developed as a quantitative and qualitative research on the oral health of schoolchildren regularly enrolled in a school unit in the city of São Luís - MA. The quantitative research was a simple random sample from an estimated two hundred and seventy students, from which the convenience group for the qualitative analysis was obtained. Results: The study showed that the students had poor oral hygiene conditions and that the educational measures applied were not sufficient to reverse the condition found in the initial evaluation. Parents/guardians resent the lack of oral health care at school, the difficulty to access the public service and the high costs of the private sector. Conclusion: It is concluded that the tooth brushing technique, although understood by the individuals, was not incorporated into the daily lives of the students because they represent a population without access to oral health care and without educational programs at the school., Therefore, it is needed the implementation of oral health policies provided by the public system with permanent actions capable of inducing the incorporation of oral hygiene practices into the students' routine.